Stimulasi Dakwah Menuju Masyarakat Qur'ani melalui KKN STIBA Makassar di Desa Alatengae Kabupaten Maros - Khaerul Aqbar; Putra Alam (WAHATUL MUJTAMA': Jurnal Pengabdian Masyarakat, 2020)
Alatengae Village on the basis of history is attached to the noble goals and ideals to always act and intend towards a better direction. The purpose of STIBA Makassar Community Service Program (KKN) III is as a form of community service which is a pillar of higher education tri dharma. The method of community service implementation in Alatengae Village began with an analysis of problems or community needs through SOAR analysis and independently created instruments. After the analysis carried out, an activity plan program was prepared which was adaptive to the needs of the community. The main program of students of STIBA Makassar Community Service Program (KKN) III in Alatengae Village were to build relation between people, teaching in elementary schools, or TK/TPA, Dirosa teaching, Islamic discouce for men and women, Tablig Akbar, Health and Cupping Seminar, and Festival for Righteous Children (FAS). The results of Community Service implementation in the form of KKN is that, in general, local people has developed in terms of Islamic knowledge, are enthusiastic in learning and has been able to read the Koran correctly, and the growth of self-confidence of students in TK/TPA in competing and high enthusiasm in enhancing interest and talent.